MODEL KIPAS : PENDEKATAN KONSELING BERBASIS BUDAYA YANG HOLISTIK DAN TERSTRUKTUR - Mosleh, Ikrimania; Khusumadewi, Ari; All Habsy, Bahkrudin; Setiawati, Denok (IKIP Siliwangi, 2025)
The Structure-Adaptive Intensive and Progressive Counseling Model (KIPAS) is an innovation in the field of guidance and counseling developed by Prof. Dr. Andi Mappiare by combining modern approaches and local wisdom of the archipelago. The model is built on five main pillars: solution-based counseling, intensive approach, progressive, culturally adaptive, and sensitivity to social structures. KIPAS uses techniques such as supportive words, constructive interpretation, reflection, direction, and problem core summarization, which are designed in accordance with Indonesian cultural values. Its implementation involves five structured steps: Good News, Data Integration, Action Planning, Actualization, and Celebration. Research shows the effectiveness of KIPAS in a variety of contexts, including education (increasing learning motivation and entrepreneurial interest) and community empowerment, with a holistic and sustainable approach. Key challenges include limited trained personnel and cultural resistance, but potential improvements, including the integration of digital technology, make the tool relevant for counseling in the modern era.